Analysis of gene function in somatic mammalian cells using small interfering RNAs - Elbashir, Sayda M.; Harborth, Jens; Weber, Klaus; Tuschl, Thomas (Methods (San Diego, Calif.), 2002)
RNA interference (RNAi) is a highly conserved gene silencing mechanism that uses double-stranded RNA (dsRNA) as a signal to trigger the degradation of homologous mRNA. The mediators of sequence-specific mRNA degradation are 21- to 23-nt small interfering RNAs (siRNAs) generated by ribonuclease III cleavage from longer dsRNAs. Twenty-one-nucleotide siRNA duplexes trigger specific gene silencing in mammalian somatic cells without activation of the unspecific interferon response. Here we provide a collection of protocols for siRNA-mediated knockdown of mammalian gene expression. Because of the robustness of the siRNA knockdown technology, genomewide analysis of human gene function in cultured cells has now become possible.